From Diagnosis to Treatment: A Literature Review on Hiatal Hernia Management - Darius Hartanto; Bradley Jimmy Waleleng; Luciana Rotty; Fandy Gosal; Jeanne Winarta; Andrew Waleleng (The Indonesian Society for Digestive Endoscopy, 2026)
A hiatal hernia is a medical disorder where the upper part of the stomach, or occasionally other intraabdominal organs, abnormally protrudes through the diaphragmatic hiatus. The occurrence of this disorder ranges from asymptomatic to severe symptoms, depending on the extent of herniation and associated complications. The development of a hiatal hernia is associated with repeated acid exposure, shortening of the muscles, and proximal displacement of the esophagus. Based on the American Foregut Society (AFS) endoscopic classification, hiatal hernia is divided into types I–IV, which guide clinical evaluation and management. Moreover, management strategies vary according to symptom severity and progression, as treatment is usually not required in asymptomatic patients. For mild to moderate cases, non-pharmacological management is recommended, such as avoidance of smoking, weight reduction, and avoidance of trigger foods and beverages. Proton pump inhibitors (PPIs) are the first-line options in pharmacological treatment, while surgical intervention is the sole method capable of repositioning herniated organs back into the abdominal cavity and addressing the functional defects related to a hiatal hernia. Therefore, this review aimed to provide a comprehensive overview of hiatal hernia management, from initial diagnosis to therapeutic selection.